SISTEM MONITORING DAYA LISTRIK BERBASIS MIKROKONTROLER AVR ATMEGA16 - Abdullah Hamdi; Arfan Eko Fahrudin; Iwan Sugriwan (Jurnal Fisika FLUX, 2013)
ABSTRACT: It has been made a monitoring power electricity based microcontrollerAVR ATMega16 for house’s tool using. The system consisted by ACS712 censor. Itable to followed the current up to 5 ampere. The voltage output from censor is followedby external filter, then went into 10 bit internal ADC by ATMega16. The value ADC iscompared with the current of censor to achieve a characteristic of sensor. The result isdisplay on LCD 16x2. It also able to do serial communication with PC that alreadyinstalled with interface program automatically, continously and directly. The resultshows the system have 94,65% accuracy.Keywords: Monitoring power electricity, censor ACS712, microcontroller ATMega16